A rare case of late onset saphenous vein graft spasm - Nirmal Guragai; Upamanyu Rampal; Rahul Vasudev; Hiten Patel; Meherwan B Joshi; Fayez Shamoon (Greater Baltimore Medical Center, 2017)
Spasm following coronary artery bypass graft surgery has been well established in arterial grafts, especially in grafts utilizing the internal mammary. Venous graft spasms are uncommon and are only observed in vein grafts during or soon after the coronary artery bypass surgery. It is exceedingly rare to see spasm of venous graft beyond one year of surgery. We report a 72-year-old female who had coronary artery bypass graft three years ago and presented with new onset chest pain for one month. The coronary angiogram revealed severe spasm of the proximal aspect of a patent saphenous venous graft which was relieved by intracoronary nitroglycerine. Patient was successfully managed using combination of anti-spasmodic medications (nitrates and calcium channel blockers) leading to long-term resolution of her anginal symptoms.